2011
DOI: 10.1158/1078-0432.ccr-11-0660
|View full text |Cite|
|
Sign up to set email alerts
|

Combining EGFR and mTOR Blockade for the Treatment of Epithelioid Sarcoma

Abstract: Purpose Molecular deregulations underlying epithelioid sarcoma (ES) progression are poorly understood yet critically needed to develop new therapies. EGFR is overexpressed in ES; using preclinical models, we examined the ES EGFR role and assessed anti-ES EGFR blockade effects, alone and with mTOR inhibition. Experimental Design EGFR and mTOR expression/activation was examined via tissue microarray (n=27 human ES specimens; IHC) and in human ES cell lines (WB and qRTPCR). Cell proliferation, survival, migrati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 38 publications
1
36
0
Order By: Relevance
“…Concordantly, combined inhibition of ERBB1/ EGFR and HGFR/MET pathways resulted in enhanced and synergic growth suppression. Thus, our observations provide an explanation for the incomplete response of VAESBJ cell line to EGFR inhibition (32).…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Concordantly, combined inhibition of ERBB1/ EGFR and HGFR/MET pathways resulted in enhanced and synergic growth suppression. Thus, our observations provide an explanation for the incomplete response of VAESBJ cell line to EGFR inhibition (32).…”
Section: Discussionmentioning
confidence: 64%
“…Recently, a role for EGFR activation has been proposed in epithelioid sarcoma (32). Although VAESBJ does not carry EGFR mutation, it displayed sustained, EGFR-independent, phospho-AKT activation, and showed limited response to EGFR inhibition (32). We found that the HGFR/MET pathway cooperates with EGFR in sustaining AKT and ERK phosphorylation.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…It is apparent that many genetic alterations found in MPNSTs lead to amplification of signal transduction pathways that enhance either JAK2/STAT3 or mTORC1/STAT3 signaling, where HIF1a lies downstream of both STAT3 and mTORC1 (28). For instance, PTEN loss is known to occur in both MPNSTs and epithelioid sarcomas (38,39) that gives rise to aberrant signaling through PI3K/mTORC1 (see Fig. 8 for signaling diagram).…”
Section: Discussionmentioning
confidence: 99%
“…The AKT/mTOR and MAPK pathways are known to be activated in some kinds of sarcomas (19)(20)(21)(22)(23), and several articles support that the AKT/mTOR and/or MAPK pathways, as well as their upstream receptor tyrosine kinases, are activated in MPNSTs (1,24,25). At least in patients with NF1, it is conceivable that Ras activation caused by Nf1 gene deficiency may induce the subsequent activation of the AKT/mTOR and Raf/MEK/ERK pathways.…”
Section: Introductionmentioning
confidence: 99%